EIB Working Paper 2022/09 - Productivity and responses to the pandemic - European Investment Bank (2022)
"The COVID-19 pandemic and its effects affected sectors in different ways, including on the firm-level productivity. Findings show that firms' responses to the COVID-19 crisis varied within sectors: more productive firms coped with the crisis better in terms of closures and employment adjustments. They were also more likely to speed up some digitalisation processes. These findings imply that the recent crisis could amplify the difference between highly productive and less productive firms. When it comes to the governments' policy measures, we find strong usage at the firm level, but very little differentiation across productivity quantiles, suggesting room for a more targeted approach for the reminder of the pandemic."